Cooling performance improvement of a two-stage pulse tube cryocooler with Er-plated screen as regenerator material. (November 2021) - Wu, Wenting; Cui, Xiaoyu; Liu, Shaoshuai; Jiang, Zhenhua; Song, Jiantang; Wu, Yinong
Highlights: A new regenerator material called Er-plated screen was proposed. Comparision between Er-plated screen and stainless steel screen were involved. Pre-cooling temperature, no-load temperature and cooling capacity were experimentally studied. A lowest temperature of 15.29K with 235W input can be achieved while using Er-plated screen. Abstract: As one of the key component in the pulse tube cryocooler (PTC), a regenerator needs to reduce losses for performance improvement. Thus, a good regenerator material should have large volumetric specific heat capacity and heat exchange area with small flow resistance. At present, high-mesh stainless steel screen and magnetic materials such as Er3 Ni are commonly used as regenerator materials in the low temperature range. However, with the cooling temperature decreasing to lower than about 20K, the volumetric specific heat capacity of stainless steel decreases significantly, increasing the irreversible heat transfer losses of the regenerator. This paper proposes a new regenerator material which coats a magnetic material (Er) with high volumetric heat capacity at low temperature on the surface of stainless steel screen. The two-stage Stirling type pulse tube cryocooler (SPTC) with Er-plated screen filled in the cold end of the second-stage regenerator is investigated. The cooling performance of the SPTC filling with stainless steel screen and Er-plated screen is compared numerically and experimentally. A no-load temperature of 14.95 K can be obtained with an electric power of W when Er-plated screen is used. The relative Carnot efficiency (rCOP) of the cryocooler with Er-plated screen at 20K is 3.32 %, which is higher than with stainless steel screen. Another interesting phenomenon found in the research is that the rCOP of the SPTC with Er-plated screen reverses to be lower than with stainless steel screen when the temperature exceeds 30 K.